Paeoniflorin inhibits human glioma cells via STAT3 degradation by the ubiquitin–proteasome pathway - Nie XH; Ou-yang J; Xing Y; Li DY; Dong XY; Liu RE; Xu RX (Dove Medical Press, 2015)
Xiao-hu Nie,1,* Jia Ou-yang,2,* Ying Xing,3 Dan-yan Li,4 Xing-yu Dong,1 Ru-en Liu,5 Ru-xiang Xu6 1Affiliated Bayi Brain Hospital, Southern Medical University, Beijing, People’s Republic of China; 2Nanchang University Medical College, Jiangxi, People’s Republic of China; 3Department of Gastroenterology, The 98th Hospital of Nanjing Military Command, Huzhou, Zhejiang, People’s Republic of China; 4Spleen & Stomach Institution, Guangzhou University of Traditional Chinese Medicine, Guangdong, People’s Republic of China; 5Department of Neurosurgery, China–Japan Friendship Hospital, Beijing, People’s Republic of China; 6Bayi Brain Hospital, The Military General Hospital of Beijing PLA, Beijing, People’s Republic of China *These authors contributed equally to this work Abstract: We investigated the underlying mechanism for the potent proapoptotic effect of paeoniflorin (PF) on human glioma cells in vitro, focusing on signal transducer and activator of transcription 3 (STAT3) signaling. Significant time- and dose-dependent apoptosis and inhibition of proliferation were observed in PF-treated U87 and U251 glioma cells. Expression of STAT3, its active form phosphorylated STAT3 (p-STAT3), and several downstream molecules, including HIAP, Bcl-2, cyclin D1, and Survivin, were significantly downregulated upon PF treatment. Overexpression of STAT3 induced resistance to PF, suggesting that STAT3 was a critical target of PF. Interestingly, rapid downregulation of STAT3 was consistent with its accelerated degradation, but not with its dephosphorylation or transcriptional modulation. Using specific inhibitors, we demonstrated that the prodegradation effect of PF on STAT3 was mainly through the ubiquitin–proteasome pathway rather than via lysosomal degradation. These findings indicated that PF-induced growth suppression and apoptosis in human glioma cells through the proteasome-dependent degradation of STAT3. Keywords: paeoniflorin, glioma, apoptosis, proliferation, signal transducer and activator of transcription 3 (STAT3), ubiquitin–proteasome pathway (UPP)